Research on Hysteresis of Piezoceramic Actuator Based on the Duhem Model - Miaolei Zhou; Jingyuan Wang (The Scientific World Journal)
To improve the modeling accuracy of piezoceramic actuator in the precision positioning system, the Duhem hysteretic model of the piezoceramic actuator was proposed. The paper used the polynomial function to approach the piecewise continuous function and f(v) and g(v) in the Duhem model, adopted recursive least squares algorithm and gradient correction algorithm to identify parameter α, polynomial coefficients of f and g in the Duhem model, and established the nonlinear parametric model of the piezoceramic actuator. Contrasting the simulation results of recursive least squares algorithm and gradient correction algorithm, the modeling accuracy is 0.24% when adopting the recursive least squares algorithm, and the modeling accuracy is 0.11% when adopting the gradient correction method. The result showed that the gradient correction algorithm could meet the modeling accuracy better, and the structure of the algorithm is simple, adaptable, and easy to implement.